Sharia Financial Literacy and the Concept of Sharia Economics Curriculum Development - Subchanifa, Dian Pujiatma Vera; Surepno, Surepno (AKUNSIKA: Jurnal Akuntansi dan Keuangan, 2025)
This research aims to analyse the level of economic literacy and Islamic finance as well as formulate concepts for sharia economics curriculum development. The research method uses a quantitative approach. A quantitative approach through questionnaires to measure the level of sharia financial literacy and obtain an overview of curriculum development models in schools. This research measures the Sharia Financial Literacy Level of High School Students and Teachers in Kudus Regency with sample data of 17 teachers and 152 students from five state high schools in Kudus Regency. From the analysis results, the financial literacy level of students and teachers falls into the sufficiently literate category. However, in terms of sharia insurance literacy, it is in the less literate category. Meanwhile, curriculum development provides an overview of development models with several approaches. The first approach is through socialisation and education; the second approach is by including Islamic economics subjects into the curriculum content structure, especially the Social Sciences department; the third approach is the application of contextual learning, namely students learn in theory and also in real practice in Islamic financial institutions; and the fourth approach is teaching Islamic accounting at school.